INFLUENCE OF SOIL MOISTURE AND SEED DEPTH ON GERMINATION AND SPEED RATE OF SOME FORAGE SHRUBS OF Chenopodiaceae - Ghufran Kattach (Mesopotamia Journal of Agriculture)
This study was carried out in a protected area at Rangeland and Dry Environment Research Station, belongs to ACSAD and Aleppo university in the Muslumieh, Aleppo, during 2005, by cultivating 9 Chenopodiaceae forage species, using 4 moisture Levels (5, 10, 15 and 20 mm), and 6 seeding depths (0, 1, 2, 3, 5 and 7 cm) and three replicates. Results showed significant effect of species, moisture and seeding depth on germination rate and speed. The seeds of all the investigated species failed to be germinated at the moisture level of 5 mm, while all the study species were germinated under 10 mm humidity except Atriplex leucoclada. The seeds of all studied species were germinated at the higher moisture levels (15 and 20 mm), but the germination percentage varied between the species. The highest germination rate for Salsola vermiculata and Seidlitzia rosmarinus was recorded when the seeds placed at soil surface and the soil moisture level 10, 15, and 20 mm. Atriplex species showed the highest germination rate at seeding depth of 1 cm and moisture level 10, 15, and 20 mm. The seeds of all studied species failed to germinate at the planting depth of 5 and 7 cm. The results showed superiority of Atriplex canescens (15.5%, 1.1) and Atriplex halimus (15.1%, 1.08) the rest of the species in terms of percentage and speed of germination, without significant differences between them, followed by Salsola vermiculata 11.8%, 0.66 and Atriplex nummularia 10.5%, 0.66, while the lowest rate and speed were recorded at Atriplex leucoclada 2.2%, 0.17, and Atriplex glauca 3.1%, 0.15. The results of statistical analysis showed the significant relation for the germination rate and the speed of the emergence of seedling with the increase in the moisture level (r=0.371 and r=0.336 respectively) and with the decrease in the depth of cultivation (r=-0.399 and r=-0.422 respectively) at P<0.001 .